SISTEM INFORMASI UJIAN SEKOLAH ONLINE SMP NEGERI 5 MEDAN BERBASIS DATA WAREHOUSE - Nikita Br Nababan; Andrian Syahputra; Sri Panca Rani; Satria Pasaribu; Bremi Br Ginting (Pixel :Jurnal Ilmiah Komputer Grafis, 2023)
Web-based information systems are in high demand in various circles of society, including in the world of non-computer education, where the written examination system commonly used in education often has many obstacles. Factors must also be considered when evaluating written tests, as many participants may avoid writing notes on cards and waste paper and ink to ask and repeat questions, including negative factors in written tests, so this study aims to do so. a database-based online exam system that educational institutions can use to convert existing written exams into an online exam system. Therefore, with the rapid development of information technology, it is necessary to design and build an online examination system based on Data Warehouse to replace the manual written examination system and facilitate the work of the teacher in SMP Negeri 5 Medan. Primary schools enter question data into the system and can minimize the operational costs of passing exams, and the system can also store data more securely in its data warehouse, i.e. teacher information, basic information, student information. subject information, value information and question information. The method is Data Warehouse, software procedures and Waterfall model. The survey respondents were 150 students from SMP Negeri 5 Medan, a total of 150 students. This online exam system was created using PHP programming language, MySQL database and XAMPP web server